2017
DOI: 10.1103/physrevd.95.025004
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic expansion of the effective potential in a functional renormalization group at finite chemical potential

Abstract: In this paper we propose a method to study the Functional Renormalization Group at finite chemical potential. The method consists of mapping the FRG equations within the Fermi surface into a differential equation defined on a rectangle with zero boundary conditions. To solve this equation we use an expansion of the potential in a harmonic basis. With this method we determined the phase diagram of a simple Yukawa-type model; as expected, the bosonic fluctuations decrease the strength of the transition.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Based on Pósfay et al (2015) and Barnaföldi et al (2017aBarnaföldi et al ( , 2017b using the FRG method we calculated the effect of bosonic quantum fluctuations on neutron star observables considering the simplest interacting Fermi-gas model and compared our results to some other similar model EoS as well. We concluded that high-order calculations are needed for the consistency between the phase diagram and the observable quantities such as the mass and radius of compact stars, compactness, and thermodynamical quantities like compressibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Pósfay et al (2015) and Barnaföldi et al (2017aBarnaföldi et al ( , 2017b using the FRG method we calculated the effect of bosonic quantum fluctuations on neutron star observables considering the simplest interacting Fermi-gas model and compared our results to some other similar model EoS as well. We concluded that high-order calculations are needed for the consistency between the phase diagram and the observable quantities such as the mass and radius of compact stars, compactness, and thermodynamical quantities like compressibility.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these calculations one can argue, that using mean field models is enough to study the neutron star data, since it is so close to the high order calculation. However, one has to be careful with such a prediction because as shown by Barnaföldi et al (2017b) the phase diagram of the model behaves differently in various approximations. The analyzed phase structure shows about 30% difference between the mean field and high order calculations.…”
Section: The Effect Of Fluctuations On Compactnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Solving the T = 0 flow equation exactly could also provide some new analytical and numerical insights. Some efforts in this direction have been done in [67], where the authors try to solve the flow equation at T = 0 by executing a mathematical transformation to the differential equations in order to transform the rectangular initial condition on a circular one, due to the Fermi sphere.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, effective theories play an important role in studying the properties of cold dense nuclear matter [14,15]. Recent studies show the importance of the correct handling of the bosonic sector in effective theories of nuclear matter [16,17], moreover, applying the functional renormalization group (FRG) method on the simplest non-trivial nuclear matter, the effect of the microscopical parameters on neutron star observables were shown in Refs. [18,19].…”
Section: Introductionmentioning
confidence: 99%